Upadłość konsumencka — doświadczenia i perspektywy - Całus, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The aim of this article is to sum up the experience to date in the area of bankruptcy procedure towards natural persons who do not conduct their own business activity, as well as to indicate the prospects for the development of the institution of consumer bankruptcy in new regulations which entered into force on 31st December 2014. The form of the Act of 29th August 2014 allows to draw the conclusion that we are dealing with a ‘new consumer bankruptcy’ which will abolish the hitherto existing barriers in the area of debt adjustments for natural persons, while simultaneously maintaining the assumption that people who run up a debt in a reckless way do not deserve to have their liabilities extinguished.
Keywords: upadłość konsumencka; regulacje prawne; postępowanie upadłościowe; osoby fizyczne